The Role Of Profitability, Liquidity, And Leverage Indicators In Predicting Financial Distress In Indonesian Property And Real Estate Firms (2022–2024) - Mulyaningtyas; Amelinda Sarah Aziilah (IJBAMS: International Journal of Business Accounting Management Social Science, 2025)
This study aims to analyze the role of key performance indicators (KPIs) in predicting financial distress in property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. The KPIs used in this study include liquidity, leverage, and profitability ratios taken from the companies' annual financial reports and annual reports. Financial distress is measured using the Altman Z-Score bankruptcy prediction model approach, which is then classified into healthy and potentially distressed categories. The research method used is a quantitative approach using secondary data with multiple regression analysis techniques to test the effect of KPIs on the probability of financial distress. The purposive technique obtained a sample of 46 companies. The results of this study indicate that certain KPIs, particularly leverage and liquidity ratios, have a negative effect in predicting financial distress, while several profitability indicators have a positive effect. These findings are expected to be taken into consideration by management, investors, and regulators in monitoring the financial health of companies in the property & real estate sector and as a basis for strengthening the early warning system for potential financial failure in the future.